Klasifikasi Data Nilai Mahasiswa Dengan Menggunakan Metode Decision Tree - Elis Sondang Dasawaty (Jurnal Informatika dan Bisnis, 2013)
In the era of globalization where technology is becoming more advanced so is necessary for an institutions or organizations to take further strategic steps, quick data processing capabilities, and produce information quickly and accurately depending on technological reliability inside those organizations. Kwik Kian Gie School of Business is one of those institutions that tries to appeal itself, and securing it’s positions more realizing the need for data mining for further use.The theory used are the meaning of data, database, data mining, system, information system, and decision tree.Data mining can be used by numerous and compatible software, during the making the following software used are : Rapidminer, PHP, Notepad++, dan xampp.The result is a program which works in a similar way to a decision tree which can give specification, or easiness during the data searching which less time consuming and gave accurate results of the wanted report .In conclusion with the existence of data mining even the existing data is uncountable, all of those data inside the organization can be easily searched, also with the use of data mining we can reduce the chances of human error.